PETA KAJIAN ORIENTALIS DALAM STUDI HADIS NABI - Annisa Az Zahra; Aufa Khofifatuz Zahroh (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2024)
This article tries to discuss the mapping of hadith studies carried out by orientalists. The study of hadith from time to time continues to develop so that the content of the transition process must be taken into account. This research uses a qualitative methodology which focuses on the use of descriptive-qualitative methodology in library research to understand hadith. So the complexity of hadith studies encourages scholars of hadith studies in both the classical and contemporary eras to come up with ideas regarding methodologies and theories that can differentiate between fake hadiths and authentic ones. This study is also practiced by Orientalists, so in practice it is not only carried out by Muslims. So this development has given rise to a new paradigm based on honesty and openness from both hadith circles and other circles.